Nanostructure and reactivity of nascent carbon particles from 2, 5-dimethylfuran/n-heptane swirling inverse diffusion flames. Issue 2 (1st February 2019) - Jia, Penghui; Liu, Dong; Ying, Yaoyao; Luo, Minye; Jiang, Bo; Zhang, Rui
Abstract: Carbon particles (Soot) have been the one of primary pollutants inevitably with the combustion of fossil fuels. A better understanding on incipient soot was useful to build the models of soot formation and even control soot emissions. The present work focuses on the nanostructure and oxidation reactivity of nascent carbon particles (soot) formed from 2, 5-dimethylfuran (DMF)/n-heptane non-swirling and swirling inverse diffusion flames (IDFs). The nascent soot samples were derived from three different fuels: 100% n-heptane, 50% n-heptane/50% DMF and 100% DMF. In addition, the effects of swirling combustion and collection time on characteristics of nascent soot were investigated in detail using the high resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). Results demonstrated that nascent soot from pure n-heptane flames presented the film-like morphology and nanostructure of amorphous nature, while the nearly primary particles with more well-organized nanostructure were found in pure DMF soot. Swirling combustion increased the entire flame front areas and diameters due to the existence of tangential velocity at the outlet of burner. Moreover, swirling combustion could enhance the mixability of the oxidizer stream and fuel stream, leading to more young soot within the fuel stream being oxidized in the inception stage. However, the collection time on soot characteristics exhibited quite negligible impacts in comparison to the swirling effects.